A colored petri nets based workload evaluation model and its validation through Multi-Attribute Task Battery-II. (April 2017) - Wang, Peng; Fang, Weining; Guo, Beiyuan
Abstract: This paper proposed a colored petri nets based workload evaluation model. A formal interpretation of workload was firstly introduced based on the process that reflection of petri nets components to task. A petri net based description of Multiple Resources theory was given by comprehending it from a new angle. A new application of VACP rating scales named V/A-C-P unit, and the definition of colored transitions were proposed to build a model of task process. The calculation of workload mainly has the following four steps: determine token's initial position and values; calculate the weight of directed arcs on the basis of the rules proposed; calculate workload from different transitions, and correct the influence of repetitive behaviors. Verify experiments were carried out based on Multi-Attribute Task Battery-II software. Our results show that there is a strong correlation between the model values and NASA -Task Load Index scores ( r = 0.9513 ). In addition, this method can also distinguish behavior characteristics between different people. Highlights: Multiple Resources theory is described with petri nets, and as a basis in model. Influences of different repetitive behaviors were considered in workload calculation. Verify experiments were conducted on Multi-Attribute Task Battery-II. The model can also reflect individual difference in behavioral characteristics.